The Developmental Axes as a Contemporary Regional Tool to Achieve Regional Parity Study Case: Syrian Coastal Countryside from Jableh to Qirdaha - بركات طارق; عضيمة ديمة (Latakia University Journal -Engineering Sciences Series, 2021)
Urban developmental axes are one of the most important developmental tools that can be followed in the developmental plans of less developing countries, which face many challenges resulting from the increasing population pressure and its continuous random growth without the existence of mechanisms to control and guide it, such as development axes that focus on infrastructure development and the creation of suitable places for development to receive new urban communities and activities. Economic and thus alleviate population pressure and its negative effects. Therefore, the research started from the concept of development axes and the bases and stages of determining them and the factors that determine their urbanization, including the points of attraction available in the region, which is the basis for determining the development axis, based on the study and analysis of some of the experiments that tried to establish and operate development axes in the world, and draw the general results necessary to be Drop it spatially on the case of the study, which is the Syrian coast countryside, as an attempt to identify the axes of urban development in which it proposes integrative activities that achieve the activation of the development axis to serve the areas passing by to ensure the spread of development from the axis to the surrounding areas.